Emergence of hypervirulent and carbapenem-resistant Klebsiella pneumoniae ST37: genomic and phenotypic characterization of virulence and resistance - Shen, Li; Han, Weihua; Huang, Yu; Wang, Shanshan; Gao, Haojin; Yang, Jinjin; Fu, Jiana; Chen, Zhixuan; Shi, Junhong; Yuan, Xinru; Yu, Jingyi; Yu, Fangyou; et al. (Frontiers in Microbiology, 2026)
The emergence and spread of carbapenem-resistant Klebsiella pneumoniae (CRKP) ST37 necessitates urgent reassessment of its pathogenic potential. This study aims to characterize the genomic and phenotypic features of ST37 isolates collected from a tertiary hospital in eastern China, from December 2020 to August 2023. Fifteen CRKP isolates underwent antimicrobial susceptibility testing, whole-genome sequencing (WGS), and phylogenetic analysis for resistance/virulence gene profiling. Phenotypic virulence assays, including quantitative siderophore production, string test, mucoviscosity, capsule quantification, serum resistance, and Galleria mellonella in vivo infection model were designed to evaluate the level of pathogenicity of the isolates. All ST37 Klebsiella pneumoniae isolates exhibited resistance to carbapenems, with 60.0% (9/15) harboring blaKPC-2 alongside extensive ESBL genes. Critically, a significant subset (26.7%, 4/15; YF1062/YF1072/YF2197/YF2203; KL25/O5) demonstrated hypervirulent phenotypes, evidenced by elevated siderophore production, aerobactin gene carriage (iucABCD/iutA), and extreme lethality in Galleria mellonella, confirming convergent ST37 CRKP-hvKP emergence. This study confirms the emergence of hypervirulent strains within the carbapenem-resistant ST37 lineage, representing a significant convergent threat necessitating urgent surveillance and novel interventions.